Academic Supervision Management of the Principal at State of Islamic Elementary School (MIN) 6 Cirebon Regency - Anugrah Imani; Ade Nurmaliyani; Dea Aulia Hani; E. Nurbaeti; Wina Verawati (Jurnal Impresi Indonesia, 2026)
This study examines the management of academic supervision conducted by the principal at MIN 6 Cirebon Regency in improving teacher professionalism and learning quality. Academic supervision is considered essential because the quality of education is strongly influenced by teachers’ instructional competence and the effectiveness of school leadership. However, many madrasahs still implement supervision conventionally, focusing more on administrative requirements than on professional teacher development. Therefore, this research aims to analyze the planning, implementation, data analysis, interpretation, and follow-up of academic supervision carried out by the madrasah principal. This study employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, vice principal of curriculum, and senior teachers. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, including data condensation, data display, and conclusion drawing. The findings reveal that academic supervision at MIN 6 Cirebon Regency is implemented systematically through supervision planning, classroom observation, competency-based assessment instruments, structured feedback, and follow-up programs such as training and mentoring. The supervision process also emphasizes objectivity, collaboration, and continuous teacher development. In conclusion, effective academic supervision management contributes significantly to improving teacher competence, instructional quality, and sustainable educational development in madrasah institutions.